(untitled) (Hanoi, 1994)
This book introduce about prcess of economic policy, economic growth in the reform process, industry in the process of economic restructuring, reforms in agriculturre, external economic relations, challenges and perspectivess of development.
Keywords: Vietnam,Vietnam,Việt Nam,Việt Nam; Economic policy,Economic conditions,Chính sách kinh tế,Điều kiện kinh tế; 1975-,1975-,1975-,1975-